Analisis Perencanaan Strategi Sistem Informasi Dalam Upaya Keunggulan Bersaing pada Apotek Kimia Farma - Elsaddhai Elsaddhai; Augie David Manuputty (APTIKOM SUMSEL, 2021)
In the current era, a development strategy is needed that can determine the success of all aspects of the business. If the company determines a strategy, problems will arise. In determining a business development strategy, it must be adjusted to the development of the current business situation, because even though the chosen strategy is very good, the situation and conditions are not supportive, then the strategy will fail. This study aims to develop IS / IT strategic planning in competing to increase pharmacy excellence, This research was conducted using the Ward and Peppard method and using the SWOT, Value Chain. The data taken are what factors can be strengths, weaknesses, opportunities, threats, and internal and external environmental analysis at the Kimia Farma Pharmacy Salatiga.